Datasets: Structured authoring for AR-based communication to enhance efficiency in remote diagnosis for complex equipment - Fernández del amo blanco, Iñigo (Cranfield University, 2020)
Datasets response variables and interaction factors have been described in https://doi.org/10.1016/j.aei.2020.101096
Keywords: 'Augmented Reality,'; 'maintenance factors'; 'diagnosis methods'; 'Remote Collaboration'; 'Efficiency Comparison'; 'Performance Evaluation; Testing and Simulation of Reliability'; 'Input; Output and Data Devices'; 'Analysis of Algorithms and Complexity'; 'Applied Computer Science'; 'Computer-Human Interaction'; 'Data Structures'